THE ONTO-GEOGRAPHICAL STRUCTURE OF WORLD-CULTURE AND THE POSITION, HE POSITION, OPPORTUNITY AND TASK OF AFRICA - Beck, Henrich (HUMANITAS DIGITAL, 2022)
Introduction Any development of Africa demands a creative coopera tion a with other continental cultures. Therefore, the specific opportunity and task of Africa within the modern world depends on its position in the geographical structure of world culture, which we now have to analyze. In this context, as relevant basical cultures we will take in consideration primarily the extensive cultural areas of the continents Europe, Africa and Asia. Also the cultures of America and LatinAmerica seem to be founded in an amalgamation of these great basical cultures; so we will confine our analysis to them. Our consideration shall be divided into the following steps: In the first place, we put up the hypothesis that the regions of culture differ due to their natural basis. In a second part, this hypothesis has to be substantiated and differentiated by pointing at corresponding cultural phenomena. Thirdly we will ask, how the cultural differentiation of mankind has to be understood ontologically, i. e. in the deeper character of its being. Finally, we have to summarize the practical result of our analysis for a creative encounter of the world cultures and for the opportunity and task of Africa.